Sex-specific differences in atherosclerosis, thrombospondin-1, and smooth muscle cell differentiation in metabolic syndrome versus non-metabolic syndrome mice - Gupta, Shreya; Khanal, Saugat; Bhavnani, Neha; Mathias, Amy; Lallo, Jason; Kiriakou, Ariana; Ferrell, Jessica; Raman, Priya (Frontiers in Cardiovascular Medicine, 2022)
Metabolic syndrome (MetS) amplifies risks of atherosclerosis. Despite well-known sexual dimorphism in atherosclerosis, underlying mechanisms are poorly understood. Our previous findings highlight a proatherogenic protein, thrombospondin-1 (TSP-1), in hyperglycemia- or hyperleptinemia (mimicking obesity)-induced atherosclerosis. However, role of TSP-1 in development of atherosclerosis prompted by co-existing hyperglycemia and obesity, characteristic of MetS, is unknown. The goal of this study was to examine sex-specific differences in lesion progression in a model of combined MetS and atherosclerosis (KKAyApoE) and interrogate how these differences relate to TSP-1 expression. Male and female KKAy+/-ApoE-/- (with ectopic agouti gene expression) and age-matched non-agouti KKAy-/-ApoE-/- littermates were placed on standard laboratory diet from 4-24-wks-age. Metabolic profiling confirmed MetS phenotype of KKAy+/-ApoE-/-; however, only male genotypes were glucose intolerant with elevated VLDL-cholesterol and VLDL-triglyceride levels. Aortic root morphometry demonstrated profound lipid-filled lesions, increased plaque area and augmented inflammatory and SMC abundance in MetS vs non-MetS males. This increase in lesion burden was accompanied with elevated TSP-1 and attenuated LMOD-1 (SM contractile marker) and SRF (transcriptional activator of SM differentiation) expression in male MetS aortic vessels. In contrast, while lipid burden, plaque area and TSP-1 expression increased in MetS and non-MetS female mice, there was no significant difference between these genotypes. Increased collagen content was noted in MetS and non-MetS genotypes, specific to female mice. Measurement of plasma testosterone revealed a link between the atherogenic phenotype and abnormally high or low testosterone levels. To interrogate whether TSP-1 plays a direct role in SMC de-differentiation in MetS, we generated KKAy+/- mice with and without global TSP-1 deletion. Immunoblotting showed increased SM contractile markers in male KKAy+/-TSP-1-/- aortic vessels vs. male KKAy+/-TSP-1+/+. In contrast, TSP-1 deletion had no effect on SM contractile marker expression in female genotypes. Together, the current study provides evidence for a role of plasma testosterone in sex-specific differences in atherosclerosis and TSP-1 expression in MetS vs non-MetS mice. Our data suggest a sex-dependent differential role of TSP-1 on SMC de-differentiation in MetS. Collectively, these findings underscore a fundamental link between TSP-1 and VSMC phenotypic transformation in MetS.